Performance, Identity, and Social Space: Theatre as a Medium of Cultural Negotiation - Taufik, Muhammad; Nieminen, Mikko; Lehtonen, Laura (Yayasan Adra Karima Hubbi, 2026)
Background. Theatre has long been a powerful medium for cultural expression, offering a space where social realities, identities, and ideologies are negotiated and contested. As a form of performance, theatre allows for the exploration of complex themes such as power, gender, race, and class, providing insights into the dynamics of cultural change. In today’s globalized world, where cultural identities are continuously reshaped, the role of theatre as a space for cultural negotiation is more significant than ever. Purpose. This research seeks to investigate how theatre functions as a medium for negotiating social identity and power in contemporary contexts. The primary aim of this study is to examine how performance, through theatre, mediates and challenges cultural identities within specific social spaces. The research explores how theatrical performances facilitate cultural negotiations and offer critical commentary on societal issues such as identity formation, power structures, and social relations. Method. This study employs a qualitative research approach, utilizing case studies of selected theatre performances from various cultural contexts. The research combines textual analysis of performance scripts with observations of live performances, focusing on the themes of identity, power, and social space. Results. The study finds that theatre serves as an active site for cultural negotiation, where performances reflect and challenge societal norms, fostering dialogue around issues of identity and power. Theatre provides a dynamic space for addressing the complexities of social relations and cultural change. Conclusion. Theatre remains a vital medium for negotiating cultural identities and power structures. Its potential to challenge dominant narratives and promote social reflection highlights its enduring significance in contemporary cultural discourse.